The United States : Spillover Report: 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2011)
The size of the U.S. economy and, in particular, the global dominance of its financial markets creates uniquely large policy spillovers. Concerns that the end of QE2 could lead to a rapid reversal of emerging market capital flows appear overblown. A credible plan for a gradual U.S. fiscal consolidation would likely have limited short-term spillovers and substantial longer-term benefits. Overall, U.S. and foreign goals appear better aligned for U.S. fiscal and financial policies than for monetary policies. Fiscal consolidation and sounder financial regulation will help.